The Influence of the Independent Teaching Platform and Digital-Based School Management on the Teaching Quality of High School Teachers - Aisyah, Helda Lara; Harapan, Edi; Rahman, Andi (PPSDP International Journal of Education, 2025)
This study aims to find out the extent of the ability of teachers in schools to use the independent teaching application. That way, it can also be known what obstacles arise in the implementation of the independent curriculum with the use of the independent teaching application and how digital-based school management can play a role in improving the quality of teachers in teaching. The study used a quantitative research motto with a sample of 95 high school teacher respondents in Seberang Ulu II district, Palembang. Partially, their teaching platform and digital-based school management have a significant effect on the quality of teacher teaching. Meanwhile, simultaneously (Together) the independent teaching platform and digital-based school management have a significant effect on the quality of teacher teaching. This can be seen from the value of the f test where f is calculated as 59.910 and the value of f table is 3.09 so that the value of f calculation is greater than that of f table. This means that the variables of the Independent Teaching Platform and digital-based school management have a positive and significant effect on the quality of teacher teaching.